CONTROVERSIES IN ASSISTED REPRODUCTION - Rizk, Botros; Khalaf, Yakoub ([S.l.] : CRC PRESS, 2020)
Assisted Reproduction is a specialty undergoing rapid change as new technologies are introduced and new research challenges previous treatment options. This text examines a selection of controversial topics for both laboratory and clinical practice and tries to place them in perspective, so readers can understand how and why the current state of the question has come about and how future contributions to the debate should be measured. All physicians involved with the technologies concerned will learn from the expert contributions assembled here.CONTENTS: The use of ovarian markers * Use of molecular markers of endometrial receptivity * Use of GnRHa for triggering final oocyte maturation during ovarian stimulation cycles * Use of time-lapse embryo imaging in assisted reproductive technology practice * Use of cryopreservation for all embryos * Preimplantation genetic screening * The use of single embryo transfer * Use of luteal phase support * Measuring safety and efficiency in in vitro fertilization * To flush follicles during egg collection or not * Use of blastocyst culture * Use of mitochondrial donation * Controversies in recurrent implantation failure: From theory to practice * Fibroids: To remove or not? * Limitations of endometrioma surgery in in vitro fertilization: Possibilities of early disease control
Foreword List of contributors 1 The use of ovarian markers Neena Malhotra and Siladitya Bhattacharya 2 The use of molecular markers of endometrial receptivity Alejandro Rincon, David Bolumar, Diana Valbuena, and Carlos Simon 3 The use of GnRHa for the Triggering of Final Oocyte Maturation during Ovarian Stimulation Cycles Dalia Khalife, Jad Farid Assaf, and Johnny Awwad 4 The use of time-lapse embryo imaging in ART practice Fadi Choucair, Chantal Farra, and Johnny Awwad 5 The use of cryopreservation for all embryos Samuel Santos-Ribeiro, Shari Mackens, Biljana Popovic-Todorovic, Annalisa Racca, Christophe Blockeel, and Panagiotis Drakopoulos 6 The use of Pre-implantation Genetic Screening Yusuf Beebeejaun and Sesh Sunkara 7 The use of Single Embryo Transfer Abha Maheshwari 8 The use of luteal-phase support Laura Melado, Barbara Lawrenz, and Human Fatemi 9 Measuring Safety and Efficiency in IVF Nicole C. Michel, Natalie Shammas, and Shima Elbakhit Albasha 10 To Flush Follicles during Egg Collection or not? Hans-Peter Steiner 11 The use of blastocyst culture Mohamed A. Aboulghar and Mona M. Aboulghar 12 The use of mitochondrial donation Andy Greenfield 13 Controversies in recurrent implantation failure: from theory to practice Efstratios Kolibianakis, Pavlidi Olga, and Christos A. Venetis 14 Fibroids -- to remove or not? Abdel-Maguid Ramzy 15 Limitations of Endometrioma Surgery in IVF: Possibilities of Early Disease Control Vasilios Tanos and Elsie Sowah Index
OCLC-licensed vendor bibliographic record.
Keywords: Reproductive technology; Reproductive technology -- Moral and ethical aspects; MEDICAL / General; MEDICAL / Gynecology & Obstetrics; MEDICAL / Reproductive Medicine & Technology